Defensoria Pública do Estado de São Paulo: profissão e política na atuação em tutela coletiva - Souza, Clarissa Christianne Rodrigues (Universidade Federal de São Carlos, 2019)
This dissertation investigates the means by which the practice of the Public Defender’s Office of São Paulo on collective and social rights sets up a political role for the institution. This role makes the institution different from the private lawyering and more similar to the political power of the Public Ministry in Brazil and to the activism of the cause lawyering. It also analyses the activism of the public defenders in setting up this institutional role and how they have been proceeding on collective and social rights in both judicial and extrajudicial arenas. The discussion is based on the sociology of professions and recent researches about legal professions and institutions operating in the social rights arena. This study is based on qualitative and quantitative data such as interviews with public defenders, statistics produced by the institution and data from judicial decisions taken between 2009 and 2017 on class actions filed by the Public Defender’s Office of São Paulo. The results show that the legitimacy for proposing class actions is seen as a political power by the public defenders, even though they have been used as a last resource in the negotiation between the State and the social demands. Mostly, the institution has been setting up its legitimacy and strength through the defense of human rights, the closeness to vulnerable people and their social demands and also through extrajudicial means of negotiating solutions.
Public Defender’s Office of São Paulo: profession and politics in collective rights
Keywords: Defensoria Pública; Ativismo jurídico; Tutela coletiva; Sociologia das profissões; Public Defender’s Office; Legal activism; Collective rights; Sociology of professions; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS